URGENSI AKSELARASI PENJAMINAN MUTU PERGURUAN TINGGI KEDINASAN MELALUI PELAKSANAAN AKREDITASI - Subiyakto, Aang (UHN IGB Sugriwa Denpasar, 2024)
The fact is that issues related to change, complexity and uncertainty have had a significant impact on the world of higher education, including official college. This implies the importance of the ability to survive, adapt and compete from the college in line with the dynamics of current developments. Regardless of the various problems, it has been proven that the official colleges are a national asset that has an important and strategic role in the development of human resources in Indonesia. The purpose of this descriptive paper was to explain the urgency of implementing quality assurance among the official colleges through accreditation. Descriptive analysis was carried out based on studies and related laws and regulations. This paper showed that accreditation is important because it is related to aspects of quality assurance, legitimacy and credibility, international recognition, access to public and private funds, transfer and acceptance opportunities, and improving quality and accountability. The use of reference materials, techniques and depth of descriptive analysis may certainly be different from other similar studies. However, this paper may be one of reference materials for stakeholders, especially in addressing the need to accelerate the quality assurance efforts of official college through accreditation.